Hitler's strategy - Hinsley, F. H. (Francis Harry) 1918- (Cambridge University Press, 2013)
First published in 1951, this book examines Hitler's strategy and how it developed during the Second World War. Hinsley, who had worked as a code breaker during the war, uses a variety of contemporary documents as sources, including records taken from the German Naval Archives after its capture by the Allies in 1945. This book will be of value to anyone with an interest in military history in general or the Second World War in particular.